2015
DOI: 10.1016/j.sajb.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The presence of usnic acid does not protect the lichen Cladina arbuscula subsp. mitis against the long-term copper excess

Abstract: a b s t r a c tCladina arbuscula subsp. mitis grows on the surfaces of historical Cu-mine spoil heaps rich in Cu, as well as on the surfaces of substrata that are not metal contaminated. This lichen contains the extracellular secondary metabolite, usnic acid (UA), which was previously found to form complexes with metal cations, including Cu. As UA can be experimentally removed from dry lichen thalli using acetone and without the loss of lichen viability, this study attempted to evaluate its role in long-term (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…mitis and P. rufescens (Bačkor et al 2009(Bačkor et al , 2011. A time-and dose-dependent decrease in the content of soluble proteins was demonstrated in an experiment with Cu excess lasting 8 weeks (Bačkorová et al 2015). In our experiment, we obtained similar results: the content of soluble proteins decreased during 2-8 weeks of exposure to conditions of excessive Cu.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…mitis and P. rufescens (Bačkor et al 2009(Bačkor et al , 2011. A time-and dose-dependent decrease in the content of soluble proteins was demonstrated in an experiment with Cu excess lasting 8 weeks (Bačkorová et al 2015). In our experiment, we obtained similar results: the content of soluble proteins decreased during 2-8 weeks of exposure to conditions of excessive Cu.…”
Section: Discussionsupporting
confidence: 84%
“…High content of Cu can cause a decrease of chlorophyll a in lichens (Puckett 1976;Bačkor et al 2003), which leads to disturbed integrity of the photosynthetic apparatus. Bačkorová et al (2015) tested the effect of Cu excess in a long-term experiment and, as in the present study, observed a decrease of chlorophyll a integrity and other photosynthetic parameters during the 8 weeks of their experiment. Values between 1.2 and 1.4 are typical for healthy lichen thalli, and a gradual decrease was observed in our experiment after exposure to the higher tested Cu dose in both thallus variants over the course of 8 weeks.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, lichen communities growing in metal-rich ultramafic alpine areas may exhibit differences in terms of secondary metabolite production compared to those of adjacent non-ultramafic areas (e.g., lower frequency of species with depsidones) [45]. However, in other cases, lichen acids play no role in protection of thalli against airborne heavy metal pollutants [46] or against metals taken from a substrate [47]. Factors other than secondary metabolites may also affect metal accumulation as shown by two closely-related species containing the same lichen acid and growing in the same habitat but having dramatically different heavy metal concentrations [32].…”
Section: Introductionmentioning
confidence: 99%